Influence of substrate type on the efficiency of horizontal and vertical subsurface flow constructed wetlands for the treatment of domestic wastewater (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
This systematic review (Scopus, 2015–2024) and bibliometric analysis assess the influence of substrate in subsurface constructed wetlands (horizontal and vertical) for treating domestic wastewater. Nine media were compared: gravel, zeolite, biochar, steel slag, volcanic rock, expanded clay (LECA), laterite, ceramic/brick, and sugarcane bagasse. Evidence indicates that the granular matrix not only provides structural support but also governs filtration, adsorption/ion exchange, precipitation (P), and biofilm development, thereby conditioning BOD/COD and nitrogen removal. For phosphorus, steel slag, laterite, and ceramic outperform inert media; for nitrogen, biochar and bagasse supply carbon for denitrification, while zeolite enhances ammonium retention. A stratified design is proposed with replaceable reactive layers (for P) and carbon amendments (10–30%) for N, tailored to local objectives and resource constraints. Bibliometric mapping shows growth since 2018 and an emphasis on alternative substrates and process intensification. The study concludes that strategic selection and layering of substrates can match or surpass classical design variables.